An evaluation of the use of caries risk/susceptibility assessment in an undergraduate dental curriculum - Melanie Nasseripour; Adam Hasan; Liz Chapple; Anusha Chopra; Lucy Cracknell; Zahraa Maiter; Aviijit Banerjee (Frontiers Media S.A., 2024)
There has been a paradigm shift in patient care with regards to delivering better oral health, towards a team-delivered, person-focused, risk-related model that is known as minimum intervention oral care (MIOC). Student skills should be developed within the undergraduate dental curricula to ensure that graduating dentists and other oral healthcare team members are able to provide phased personalised care plans alongside behavioural management support to patients/caregivers to prevent and manage oral disease in the long term. The purpose of this study is to establish that using an adjunctive caries risk/susceptibility assessment (CRSA) technology (PreViser) had an impact on the behaviour, perception, and knowledge of dental undergraduate students and their clinical teachers, regarding the benefits of such an oral health assessment in the management of patients. Four cohorts of students who did not have exposure to the caries risk susceptibility software were compared with those who did. This study was conducted using a mixed methods approach using a convergent parallel design consisting of collecting quantitative data through questionnaires presented to four cohorts of Year 4 dental students (n = 150 per cohort) and their clinical teachers (n = 10) and qualitative data from structured interviews with students (n = 5) and teachers (n = 7) with suitable statistical analysis and interpretation.ResultsGenerally, the items that exhibited statistical significance, when reviewed, showed better behaviour, perception, and knowledge towards CRSA in the Group C (BDS4-22T1) cohort in comparison with the Group A (BDS3-20T2) cohort. The Group D (BDS4-22T2) students felt more confident using the PreViser as a CRSA tool. When comparing the Group C and Group D data, we note that the students from the Group C cohort were more likely to carry out a diet analysis for their patients and were less likely to be negatively impacted by time constraints compared with the Group D students. Both cohorts were equally confident in using the PreViser for CRSA. From a qualitative perspective, although competence and confidence appeared high, the students and teachers acknowledged that they would need more support to use it chairside. The main barrier listed to using PreViser rested in the fact that clinical teachers either preferred their own ways of assessing or did not know how to use the tool and therefore did not encourage using it. Those who did use PreViser highlighted that it was straightforward to use and was a systematic approach, enabling communication with the patients as there is 'evidence' to back up the clinical recommendations.ConclusionThe cumulative benefit of training and use (even limited) had an impact on the students' knowledge, competence, and confidence regarding CRSA, ultimately facilitating the process of teaching and assisting them in effectively implementing CRSA. The importance of CRSA became more evident immediately following the training. Further research is suggested to understand the factors influencing student behaviour, perception, and knowledge regarding CRSA with the aim to make recommendations on a preferable approach and tool to help streamline CRSA education.